Retrospective Cohort Study: Severe COVID-19 Leads to Permanent Blunted Heart Rate Turbulence - Mücahid Yılmaz; Çetin Mirzaoğlu (Diagnostics)
Background: Heart rate turbulence (HRT) is a non-invasive technique that can be used to evaluate autonomic nervous system (ANS) function and cardiac arrhythmia. The objective of this study is to investigate whether COVID-19 can lead to long-term blunted HRT following recovery. Methods: This retrospective cohort study included 253 individuals with a confirmed history of COVID-19, referred to as the recovered COVID-19 group, along with 315 healthy participants who had no history of the virus. The recovered COVID-19 group was categorized into three subgroups based on their chest CT severity scores. The HRT analyses were obtained from a 24-h electrocardiography-Holter recording. Results: This study revealed that the HRT onset value was elevated in the recovered COVID-19 group, while the HRT slope value showed a significant decrease when compared to the control group. Correlation analyses indicated a positive relationship between the chest CT severity score and HRT onset, whereas a negative correlation was observed between the chest CT severity score and HRT slope. Regression analyses identified recovery from severe COVID-19, chest CT severity score, hypertension (HT), and smoking as independent predictors of both abnormal HRT onset and the existence of an abnormal HRT slope. Conclusions: Individuals who have recovered from severe COVID-19 are expected to encounter a permanent blunting of HRT, which is regarded as a significant indicator of an increased risk of ventricular arrhythmias and impaired autonomic nervous system (ANS) function. Recovered severe COVID-19 individuals should be carefully evaluated for HRT with 24-h ECG-Holter.